Microstructure, mechanical properties, and drop reliability of CeO2 reinforced Sn-9Zn composite for low temperature soldering - Sharma, Ashutosh; Srivastava, Ashok K.; Ahn, Byungmin (Materials Research Express, 2019)
In this study, CeO2 reinforced eutectic Sn-9Zn-xCeO2 composite specimens were prepared by mixing and melting route. The CeO2 nanoparticles were synthesized by chemical precipitation method. The composite samples were produced by adding CeO2 nanoparticles from, x = 0, 0.3, 0.6 to 0.9 wt% in the eutectic Sn-9Zn matrix. The microstructural analysis revealed that the presence of CeO2 in Sn-9Zn-xCeO2 matrix refined the Zn needles when CeO2 was added up to x = 0.6. The wetting properties of these solders were considerably enhanced (≈17%) over monolithic Sn-9Zn alloy. The melting properties of Sn-9Zn-xCeO2 solders showed a narrow pasty range 3.9 °C-7.6 °C. The mechanical strength and ductility of the solders were also improved after addition of CeO2 nanoparticles in the matrix up to x = 0.6. An optimum fraction of 0.6 wt% CeO2 in eutectic Sn-9Zn alloy is recommended to obtain a set of enhanced wetting, strength and drop reliability of Sn-9Zn solder.
Keywords: CeO2; CeO2 nanoparticles; Chemical precipitation method; Composite specimens; Low temperature soldering; Melting properties; Microstructural analysis; Strength and ductilities; CeO2; composite; intermetallic compounds; Lead free solder; reliability